Impact of acceptor-type substitution on electrical transport properties of zircon-type EuVO4. Issue 1 (January 2018) - Gayathri, Thozhuthungal Haridasan; Yaremchenko, Aleksey A.; Zakharchuk, Kiryl; Abhilash, Pullanchiyodan; Ananthakumar, Solaiappan
Abstract: Magnesium-substituted europium vanadate ceramics, Mgx EuVO4 ± δ ( x  = 0–0.5), were prepared by solid state method and characterized by XRD, SEM/EDS, dilatometry, UV–vis spectroscopy, impedance spectroscopy, and measurements of oxygen-ion transference numbers ( t o ¯ ). Magnesium was found to substitute preferentially into vanadium sublattice of zircon-type EuVO4 with limited solubility of ∼5 at.%. Additions of magnesium increase slightly coefficients of thermal expansion (3.2–6.0 ppm/K at 150–400 °C) and have negligible effect on the optical properties. Undoped EuVO4 is predominantly an oxygen-ionic conductor with t o ¯  = 0.96–0.99 at 700–900 °C under oxidizing conditions. Acceptor-type substitution suppresses total conductivity and oxygen-ionic transport. The variations of electrical transport properties are discussed in terms of interstitial oxygen diffusion in the parent EuVO4 and oxygen vacancy diffusion in Mg-substituted vanadate. Humidified atmosphere has negligible impact on the electrical properties of substituted ceramics but results in increased electrical conductivity of EuVO4 indicating a protonic contribution to the total electrical transport.